1994
DOI: 10.1017/s0022112094000297
|View full text |Cite
|
Sign up to set email alerts
|

Drop formation during coating of vertical fibres

Abstract: When the coating film around a vertical fibre exceeds a critical thickness hc, the interfacial disturbances triggered by Rayleigh instability can undergo accelerated growth such that localized drops much larger in dimension than the film thickness appear. We associate the initial period of this strongly nonlinear drop formation phenomenon with a self-similar intermediate asymptotic blow-up solution to the long-wave evolution equation which describes how static capillary forces drain fluid into the drop. Below … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
164
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(169 citation statements)
references
References 12 publications
5
164
0
Order By: Relevance
“…Kalliadasis and Chang [5] solved the evolution equation derived by Frenkel [4] and showed that the mean flow can arrest the drop formation process when the thickness of the film is less than the critical value, h c , observed by Quéré [3] in which h c ∼ a 3 H −2 , where H = (σ/ρg) 1/2 . The nonlinear dynamics of Frenkel's equation has also been investigated by Kerchman and Frenkel [6] and Chang and Demekhin [7].…”
Section: Introductionmentioning
confidence: 99%
“…Kalliadasis and Chang [5] solved the evolution equation derived by Frenkel [4] and showed that the mean flow can arrest the drop formation process when the thickness of the film is less than the critical value, h c , observed by Quéré [3] in which h c ∼ a 3 H −2 , where H = (σ/ρg) 1/2 . The nonlinear dynamics of Frenkel's equation has also been investigated by Kerchman and Frenkel [6] and Chang and Demekhin [7].…”
Section: Introductionmentioning
confidence: 99%
“…Frenkel derived a simple Benney-like equation for the evolution of the film thickness using a thin-film approximation [8]. The nonlinear dynamics of Frenkel's equation has also been investigated by Kalliadasis and Chang [9], Kerchman and Frenkel [10], and Chang and Demekhin [11].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the precursor film thickness to η = 0.01 has marginal effect; increasing by a further order of magnitude (Figure 11(c)) increases drop speeds but again causes drops in vertical tubes to fall increasingly slowly compared to tilted tubes. We infer that the drop dynamics are controlled by a balance between dissipation at the advancing contact line and release of potential energy (as in [5,10]), so that wider drops are subject to greater dissipation and therefore travel slower. (In the most extreme case, α = π/2 in figure 11(d), the front of the drop wraps entirely around the interior of the tube to become a collar for t 8.)…”
Section: Motion Of An Isolated Dropmentioning
confidence: 98%
“…[13] (exploiting the fact that, to leading order, substrate curvature in a curved tube has the same effect as gravity in a straight tube) and [16] (who included higher-order terms); the limit α = π/2, ∂ θ = 0 was considered in, for example, refs. [5,6,20]. Full details of the derivation of this class of equation may be found in these earlier works.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation